Cytokine profile and clinical metabolic alterations in HIV-1 infected individuals with and without lipodistrophy - Pontes-Cardoso,L. C. R. (2007)
The extensive use of Highly Active Antiretroviral Therapy (HAART) has transformed HIV infection into a chronic condition. Thus, metabolic alterations including lipodystrophy and dyslipidemia have been associated with the use of such medications. The objective of the present study was to analyze clinical metabolic alterations and the profile of TNF-alpha, IFN-Y, IL-2, IL-10, and TNF-alpha type II soluble receptor in serum of HIV-1 individuals with and without lipodystrophy. Eighty-four adults were evaluated, 42 males and 42 females, mean age 37 years, and HAART time of at least 15 months. Two groups were formed, G1: 42 individuals with lipodystrophy, and G2: 42 without lipodistropy. From the HAART used, stavudine was more associated with the lipodystrophy group and zidovudine with the non-lipodystrophy group. CD4 and CD8 values, viral load, glucose, albumin, and lipids were not different between groups, except for triglycerides, which were high in the lipodystrophy group, and HDL, whose concentration was reduced in G1. TNF-alpha, TNF-RII, and IL-10 profiles were high and had positive correlation; IL-2 and IFN-gamma had reduced levels in the lipodystrophy group. High TNF-alpha and its receptor levels seem to be associated with lipodystrophy development in individuals under HAART therapy.